Presenting a Model for the Role of Digital Marketing in Developing Institutional Performance (case study of Maysan Oil Company - Iraq) - Radhi, Hasanain Mohammed; Zarei, Gassem; Kolour, Hossein Rahimi; Ayirlou, Mohammad bashokouh (Journal of Posthumanism, 2025)
The current research is entitled The Role of Digital Marketing in Developing Institutional Performance A Case Study in Maysan Oil Company. The purpose of the research is to develop institutional performance as a whole or some of dimensions through the optimal use of digital marketing channels and dimensions. To achieve this purpose, data were collected, a comprehensive literature review conducted, and experts were consulted. The current research follows a mixed approach to analysis, based on a philosophical approach that emphasizes construction and interpretation as concepts arising from social interactions. This framework serves as the basis for the research. In the first stage, inquiries were posed to a number of university professors, managers, and specialized employees (as experts) in this field. Uses an inductive model to develop a methodological structure referred to as the grounded theory, which provides a strong foundation for the research. In addition, includes content analysis. This process allows us to analyze qualitative information through coding and by assessing the approaches and strategies that can be used to address the research questions. Following that, using the information from the initial analysis phase, the descriptive analysis process begins by publishing questionnaires. (360) questionnaires were published to managers and employees in the oil company who represent the research community, then the answers were analyzed in several statistical programs to reach accurate results. The study found a strong statistically significant relationship that digital marketing plays a fundamental role in developing institutional performance. Improving the marketing performance of the institution and using the digital promotional mix, which always aims to reach the organizations’ products to a wide segment of customers as they are the important number in the organization, communicating with customers through digital marketing channels that suit each customer individually, improving financial performance and increasing income for organizations. Finally, successful performance is the final result that the organization aims to achieve by achieving its long-term goals that contribute to the development of institutions, which makes institutions strive to search for new means that keep pace with technological developments through which they seek to improve their performance.